Social, Cultural and Educational Evolution of Kaibarta Community in Assam - Konwar, Poli (Current Progress in Arts and Social Studies Research Vol. 8, 2024)
Assam is one of the old states of India. This region marked by significant ethnic diversity, has historically encompassed a blend of tribal and non-tribal communities, contributing to a complex social landscape. It is to be noted that the non-tribal category is included into three major groups such as the General Caste, the Scheduled Castes (SC) and the Other Backward Classes (OBC). There are sixteen SC, twenty seven Scheduled Tribes (ST) and twenty nine OBC communities listed in Assam. The people of all communities are peace loving and are focused on maintaining social peace and harmony in the region. They have moved away more or less from their traditional social lifestyle. The members of the Kaibarta community play a very important role in the overall development of Assam. The traditional culture and heritage of the Kaibarta community are rich and significant. The present study is an attempt to discuss the social, cultural and educational Evolution of the Kaibarta community in Assam. The secondary data were collected from both government and non-government publications. In order to achieve the objective of the present study, the descriptive research method was used in this work. The findings revealed that in spite of having a huge potential for development, most of the people of the Kaibarta community have remained backward even after seventy-three years of independence of the country. By now it is almost clear that the Kaibarta community in the state is faced with different social, cultural, and economic problems for development.